Sexually transmitted infections or reproductive tract infections prevalence and treatment efficacy of syndromic approach in reproductive age group women attending gynaecological out-patient department - Yadav, Amita; Deepshikha; Sonkar, Shubhangi; Sachan, Reena; Singh, Richa (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Sexually transmitted infections (STI) and reproductive tract infections (RTI) continue to be a major health, social and economic problem worldwide, especially in developing countries. The aim of this study is to determine the prevalence of STI and RTI among women of reproductive age (18-49 years) attending gynaecological consultations. Methods: A cross-sectional study of 1006 women of reproductive age attending a hospital was conducted over a period of 1 year. Out of these 116 women were not followed up, so they were excluded from the study. Thus, 890 women between the ages of 18 and 49 who were fertile completed the study, whether or not they had symptoms. Results: According to a laboratory test, the overall prevalence of STDs and STIs in women of childbearing age was 24.62% in symptomatic individuals and 12% in asymptomatic individuals. Vaginal discharge (61.91%) was the most common symptom Conclusions: To reduce the prevalence of STIs, RTI /STI screening for women in all reproductive age groups is essential. Early detection and treatment can reduce the severity of long-term sequelae and prevent complications.